The mortal god: imagining the sovereign in colonial India - Banerjee, Milinda (Cambridge University Press, 2018)
""Examines the construction of new concepts of sovereignty in late nineteenth and early-mid twentieth century India through the production of divergent visions of human, divine, and messianic rulership"--Provided by publisher"--